Diferencias en el consumo de tabaco en estudiantes según el sexo universitarios (2023)
Introduction: Tobacco consumption affects the entire population, particularly university students, who are exposed to group pressures and other factors favoring their initiation. Sex plays an important role, a reason why it is necessary to know the characteristics of consumption according to sex in order to design prevention campaigns based on the requirements of each population group. Objective: To characterize tobacco consumption in university students according to sex. Methods: Cross-sectional, descriptive study with a sample of 323 students of the programs of Business Administration, Commerce, Accounting, Nursing, Law and Psychology, in a private university of Santa Marta. The information was collected through the questionnaire Prevalence of Tobacco Consumption in University Students. Data analysis was carried out using the statistical package SPSS in its version 23 and the statistical tests Odds Ratio and Chi-square goodness of fit. Results: The prevalence of tobacco consumption was higher in men than in women, and the risk for smoking among men was 3.49 times higher than among women. Conclusions: There is a relationship between tobacco consumption and sex, a reason why the characteristics of consumption differ in men and women. This is relevant for the design of tobacco prevention programs. © 2018 Revista Cubana de Enfermería.